Production of alcohols from Olive Mill Wastewater by cultivation of some marine bacterial strains - زوان ميس (Latakia University Journal -Biological Sciences Series, 2023)
This research focuses on the use of marine bacteria in treatment of a serious environmental problem caused by liquid waste from olive mills called ( Olive Mill Wastewater : OMW) Marine bacterial strains (Staphylococcus xylosus(1), Staphylococcus xylosus(2), Bacillus cereus) were isolated from marine water and sediment to produce alcohols (methanol, ethanol, isopropanol, butanol and hexanol) from OMW. The results showed that the marine bacterial strain Staphylococcus xylosus (1) gave the highest alcohol productivity (methanol: 1427.22μg/l, ethanol: 720.45 μg/l, butanol: 187.65 μg/l, isopropanol: 11.28μg/l, hexanol: 137.31 μg/l) in a fermentation medium containing 25% OMW. In general, the results showed higher concentrations of alcohols in the fermentation medium using the strain Bacillus cereus compared to the strain Staphylococcus xylosus (2), while the concentrations of both hexanol and butanol were similar for the two bacteria with a slight increase in production for Staphylococcus xylosus (2) compared to Bacillus cereus When both were used in treatment of OMW at percent 50% in the fermentation medium. The bioremediation used in this study using Staphylococcus xylosus (1), Staphylococcus xylosus (2), and Bacillus cereus is low cost and has good effectiveness in eliminating the problem of environmental pollution caused by OMW on the one hand and the production of alcohols of applied importance in various in fields (Industrial, medical, pharmaceutical) on the other hand.